Electric potentials in magnetic dipole fields normal and oblique to a surface in plasma: Understanding the solar wind interaction with lunar magnetic anomalies. Issue 9 (14th May 2013) - Wang, X.; Howes, C. T.; Horányi, M.; Robertson, S.
Abstract : [1] We experimentally investigated the solar wind interaction with moderate‐strength lunar magnetic anomalies in which the electrons are magnetized but the ions remain unmagnetized. Previously, we studied the plasma sheaths above an insulating surface in a magnetic dipole field oriented parallel to the surface. In this paper, when the dipole field is oriented normal to the surface, the surface potential largely rises, and a potential bump forms in the sheath in the magnetic cusp region due to a significant magnetic mirror reflection of the electrons. It is also found that the electrons are shielded from the central dipole wings and diverted into the side of the wings. When the dipole field obliquely intersects the surface, an asymmetric potential distribution develops. Our experimental results indicate that lunar surface charging can be greatly modified in the magnetic anomaly regions, creating extreme local electrical environments. Key Points: Laboratory studies of solar wind interaction with lunar magnetic anomalies Studied the plasma sheath formation and surface charging in magnetic cusp Identified kinetic features across the dipole field region